APPLICATION OF TECHNOLOGY AS A SOCIAL ENGINEERING EFFORT ON THE IRON SAND MINING COMMUNITY AT THE SOUTH COAST OF WEST JAVA - Yunita, Desi (Badan Penelitian dan Pengembangan Daerah (BP2D) Provinsi Jawa Barat, 2017)
This research aim to determine the extent of mining activities have an impact on the change to society. A series of research conducted show that mining activities undertaken by the community has prompted a change in the structure, culture, and economy. The three elements that change is a direct impact of the iron sand mining. Wherein the iron sand mining activities cause the change in interaction pattern, community perspective, and also rise the new social groups. Cultural change can be observed from the changes of the community livelihood system that also affect to the community relation pattern. Whereas economic changes are indicated by the sift of livelihood, but it doesnât significantly change the economic condition. The application of technology has successfully encourage a change of perspective, attitude, mindset, increase incomes in the economy, and encourage environmentally friedly mining practices.Â